2001
DOI: 10.1260/0263617011494312
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Promoted Catalysts in the Reforming of n-Butane with CO2 or H2O

Abstract: Studies of the reforming of n-butane by steam and carbon dioxide have been undertaken employing commercial catalysts such as Ni/a-Al 2 O 3 modified by small additions of promoters such as K, Ba, Ce, W and Mo compounds. It was found that promoters improved the resistance of the catalyst towards coking, with this effect being smaller where CO 2 was employed in the reforming reaction than when steam was used. The dynamics of the growth of the carbon deposit on the catalyst surface depended on the promoters employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Citric acid has three carboxylic groups that can participate in the formation of bonds with nickel and cerium or tungsten. The equilibrium between citric acid and its deprotonated forms is related to the pH of the solution and nature of the ions [13,15,16] , which can be adsorbed on alumina support [30]. The presence of citric acid may also influence viscosity during drying and calcination stages, hindering the migration of precursors, enhancing formation of "gel-like" rather than "crystalline-like" phases [31].…”
Section: Structural and Surface Properties Of Catalysts After Calcina...mentioning
confidence: 99%
See 1 more Smart Citation
“…Citric acid has three carboxylic groups that can participate in the formation of bonds with nickel and cerium or tungsten. The equilibrium between citric acid and its deprotonated forms is related to the pH of the solution and nature of the ions [13,15,16] , which can be adsorbed on alumina support [30]. The presence of citric acid may also influence viscosity during drying and calcination stages, hindering the migration of precursors, enhancing formation of "gel-like" rather than "crystalline-like" phases [31].…”
Section: Structural and Surface Properties Of Catalysts After Calcina...mentioning
confidence: 99%
“…In contrast, the effects of tungsten in catalysts used for CO 2 methanation have not been widely discussed in the literature, although the beneficial role of tungsten has been revealed in other reactions, including the steam and dry reforming of hydrocarbons [14][15][16]. The impact of tungsten promoter was mainly associated with an improvement in the sintering and coking resistance of the catalysts [14][15][16]. Early work of Kelley indicated that pure tungsten can be active in CO methanation reaction at low temperatures [17].…”
Section: Introductionmentioning
confidence: 99%
“…The order of activity for Rh catalyst supports was Al 2 O 3 > TiO 2 > MgO > SiO 2 , and the H 2 to CO ratio was the highest, 0.53-0.64, with the Rh/TiO 2 catalyst. Panczyk et al [13] observed that molybdenum modification of Ni/Al 2 O 3 catalyst and increase in the CO 2 /C ratio decrease carbon deposition on the catalyst in the CO 2 reforming of butane. In studies on CO 2 reforming of n-heptane on 23% Ni/Al 2 O 3 , 0.2% Ru/La 2 O 3 and 1% Ru/Al 2 O 3 catalysts, Fujimura et al [14] found the Ni catalyst to be the most active, but it was deactivated by whisker carbon formation.…”
Section: Introductionmentioning
confidence: 99%
“…Los hidrocarburos craquean térmicamente y el hidrógeno y/o el carbón resultantes actúan como iniciadores del proceso de reducción que se mantiene con el hidrógeno producido en la reacción de reformado [130]. Empleando ZrO 2 ó TiO 2 como soporte, se obtienen valores para la frecuencia turnover muy inferiores a los de los otros soportes, especialmente en el caso de la circona.…”
Section: 73-activación De Catalizadoresunclassified